2012
DOI: 10.17231/comsoc.22(2012).1273
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Media – Mobile Creativity?

Abstract: Today's society is characterized by a mobility shift in the usage of media, which influences the ways people communicate and express themselves. This paper explores the basic correlation between mobility and creative ways of mobile phone usage. The results of a study conducted among 597 students at the University of Paderborn show how mobile phone users adopt creative ways of communicating in their daily life. Furthermore, different special subgroups of mobile users and their creative actions could be identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
(10 reference statements)
0
4
0
1
Order By: Relevance
“…• Real-time communication: Relying on the mobility property, mobile devices support real-time interaction regardless of time and location [10,11] and enable users to conveniently switch between physical and digital spaces. As a result, the boundary between public and private areas is eliminated.…”
Section: Introductionmentioning
confidence: 99%
“…• Real-time communication: Relying on the mobility property, mobile devices support real-time interaction regardless of time and location [10,11] and enable users to conveniently switch between physical and digital spaces. As a result, the boundary between public and private areas is eliminated.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Kyobe et al (2022), it was discovered that the use of smartphones by students actually enhances their creativity. Ganguin and Hoblitz (2012) delved into the interplay between innovative mobile phone usage and mobility. Their research concluded that while communicating through mobile phones, users establish connections, express ideas, create and recreate content, share knowledge and develop feedback systems.…”
Section: Role Of Mobile Devices To Support Teachers' Creativitymentioning
confidence: 99%
“…Como fazer da indústria fonográfica um meio mais igualitário para os distintos atores que nela trabalham? O que pode ambicionar, nos próximos anos, um mercado artístico que está sempre se transformando com fenômenos como os da "cultura de convergência" ou "convergência de mídias", observados por tantos pesquisadores (Ganguin & Hoblitz, 2012;Noronha e Sousa et al, 2012;Piñeiro-Otero & Ribeiro, 2015)? Espera-se que este trabalho tenha respondido ou tentado iluminar algumas dessas questões e possa, assim, contribuir para um melhor posicionamento das pessoas que se interessam por este debate ou, quem sabe até, para o esclarecimento das futuras ações concretas dos agentes que fazem parte do campo musical.…”
Section: A Título De Conclusão: Rupturas E Continuidadesunclassified